Associations of urinary metabolites of oxidized DNA and RNA with the incidence of diabetes mellitus using UPLC-MS/MS and ELISA methods - Schöttker, Ben; Larsen, Emil L.; Weimann, Allan; Henriksen, Trine; Brenner, Hermann; Poulsen, Henrik E. (Free radical biology and medicine, 2022)
Background - To evaluate the association of urinary oxidized guanine/guanosine (OxGuo) levels with incident type 2 diabetes (T2D) among older adults. - Methods - A nested case-control design was applied with 440 cases of incident T2D and 440 controls, randomly sampled from all 65-75 year-old study participants of the ESTHER study, which is a population-based German cohort study with 14 years of follow-up. Analyses of 8-hydroxy-2′-deoxyguanosine (8-oxo-dGuo; DNA oxidation product) and 8-hydroxyguanosine (8-oxo-Guo; RNA oxidation product) were measured by ultra-performance liquid chromatography tandem-mass spectrometry (UPLC-MS/MS). The sum of the two OxGuo molecule concentrations was calculated and called OxGuo-UPLC-MS/MS. The corresponding OxGuo-ELISA levels were measured by Cayman's DNA/RNA oxidative damage ELISA, which detects a mix of 8-oxo-dGuo, 8-oxo-Guo and one other OxGuo molecule. Logistic regression was applied and models were adjusted for age, sex, BMI, HbA1c, and C-reactive protein levels. - Results - 8-oxo-dGuo and 8-oxo-Guo were highly correlated with each other (r = 0.642) and weakly correlated with OxGuo-ELISA (r = 0.22 and r = 0.14, respectively). OxGuo-ELISA levels were statistically significant associated with T2D incidence (odds ratio (OR) and 95% confidence interval [95%CI] for comparison of top and bottom quartile: 1.77 [1.14; 2.76]). In contrast, the ORs did not increase stepwise from quartile 2 to 4 for neither 8-oxo-Guo, 8-oxo-dGuo levels nor OxGuo-UPLC-MS/MS and comparisons of top and bottom quartile were not statistically significant. In a post-hoc analysis comparing bottom quartile 1 with a combined group of quartile 2-4, the association of OxGuo-UPLC-MS/MS with T2D incidence reached statistical significance (OR [95%CI]: 0.66 [0.46; 0.96]) and was very similar with the one obtained for OxGuo-ELISA (OR [95%CI]: 0.66 [0.45; 0.95]). - Conclusions - Although only the measurements of the DNA/RNA oxidative damage ELISA kit of Cayman were statistically significantly associated with T2D incidence in the main analysis, confidence intervals overlapped and the post-hoc analysis showed that results for OxGuo-UPLC-MS/MS were quite comparable.